DETERMINATION OF INDONESIA'S ECONOMIC GROWTH FROM MONETARY PERSPECTIVE - Muhammad Pathi Farhan (2021)
This study discusses the determinants of economic growth in Indonesia which are determined by investment, exchange rates and interest rates. This study aims to determine the effect of investment, exchange rates and interest rates on economic growth in Indonesia. Meanwhile, the results show that investments that are proven to have no effect on economic growth because there are many investments that have not been realized and investment in Indonesia only focuses on the industrial and agricultural sectors. Furthermore, the exchange rate and interest rates are proven to have an effect on economic growth because the exchange rate is one of the determining factors that play a major role in economic growth, as well as interest rates which are also one of the determinants of economic growth.